Taxonomic notes on the Cephenniini (Coleoptera, Scydmaenidae): Status of Coatesia Lea, Cephennomicrus Reitter, and Neseuthia Scott - Jałoszyński, Paweł (Zootaxa, 2008)
Based on examination of its type species, Coatesia Lea is placed as a junior synonym of the nominotypical subgenus of Cephennodes Reitter. In order to avoid secondary homonymy with Cephennodes latus (Motschulsky), Coatesia lata Lea is replaced with Cephennodes leai nomen n. Neseuthia Scott is placed as a junior synonym of Cephennomicrus Reitter. Diagnostic characters of Cephennomicrus are discussed, and a world checklist of 50 species currently recognized as belonging to this genus is provided. The following new combinations are established for species formerly placed in Neseuthia: Cephennomicrus affouchensis (Franz), C. afiamalui (Franz), C. anderssoni (Franz), C. asperus (Franz), C. cactiformis (Jałoszyński & Hoshina), C. caledonicus (Franz), C. cordithorax (Scott), C. cornutus (Scott), C. crenatus (Scott), C. dugdalei (Franz), C. fijii (Franz), C. fujianus (Jałoszyński), C. gomyi (Franz), C. hobbiti (Jałoszyński & Hoshina), C. inconspicuus (King), C. japonigenus (Jałoszyński & Hoshina), C. lauensis (Franz), C. lordhowei (Franz), C. mauritiensis (Franz), C. minimus (Franz), C. minor (Scott), C. nomurai (Jałoszyński & Hoshina), C. okinawanus (Jałoszyński, S. Arai & K. Arai), C. perexiguus (Scott), C. perthi (Franz), C. politus (Scott), C. samoanus (Franz), C. sumatranus (Franz), C. taiwanensis (Jałoszyński), C. typicus (Scott), C. upoluensis (Franz), C. venuensis (Franz), C. vitiensis (Franz), and C. zimmermani (Franz). Cephennomicrus insularis nomen n. is proposed as a replacement name for C. suturalis (Franz) comb. n. (nec Besuchet); C. perpuncillum Reitter is corrected to C. perpunctillus, and Neseuthia sumatrensis Franz is treated as an incorrect original spelling. Based on examination of the type material, Cephennium raffrayi Schaufuss is transferred to Cephennomicrus. Lectotypes are designated for Coatesia lata and Neseuthia typica.